PERAWATAN DAN PELESTARIAN ARSIP REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH KLUNGKUNG - Rani, Putu Eka; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT The purpose of this study was to determine the factors of damage to the medical record as well as how the preservation process of medical record files in the Klungkung Regional General Hospital. The method used in this paper is a qualitative research method. Data is this study were obtained through observation and interviews. The informants is this study consisted of three people consisting of the head of the medical record, the guarantor of the assembling, and the outpatient medical record affairs department of the Klungkung Regional General Hospital. The results of research observations and interviews indicate that the archive preservation activities are guided by hospital Standard Operational Procedures (SOP). Kata Kunci : Preservation, Medical Record, Hospital